Analysis of Joint Marketing Initiatives by Farm Group and its Contribution to Marketing Performance - Yuniarto, Antonius; Radyati, Maria R. Nindita (Journal of Social Research, 2023)
The agricultural industry is critical to human life, yet it is not comparable to small farmer’s income in Indonesia. The number of farmer households is decreasing, and the average age of farmers is increasing. The agricultural industry is no longer appealing to the younger generation due to a variety of issues experienced by Indonesian farmers. The majority of Indonesian farmers are small-scale, with little land and production. Farmers also face obstacles such as not having sufficient skills in agricultural business which results in low productivity and no added value to their production. This condition also causes them to have to deal with volatile prices from middlemen which are often not profitable for farmers. The Collective Marketing initiative was created to help agricultural enterprises become more lucrative by increasing the size of farmers' economies of scale, allowing them to enter a secure market with enough bargaining power. This study examines the economic and social impacts of Collective Marketing initiatives in Kopwan Srikandi, as well as in Koperasi Tani Kopi Prima Jaya and KTH Cibulao Hijau. This study also discusses the impact of the Collective Marketing initiative on sustainable development.